Bone single photon emission computed tomography (SPECT) in a patient with Pancoast tumor: a case report - Javadi, Hamid (2010)
CONTEXT: Non-small cell lung carcinomas (NSCLCs) of the superior sulcus are considered to be the most challenging type of malignant thoracic disease. In this disease, neoplasms originating mostly from the extreme apex of the lung expand to the chest wall and thoracic inlet structures. Multiple imaging procedures have been applied to identify tumors and to stage and predict tumor resectability in surgical operations. Clinical examinations to localize pain complaints in shoulders and down the arms, and to screen for Horner’s syndrome and abnormalities seen in paraclinical assessments, have been applied extensively for differential diagnosis of superior sulcus tumors. Although several types of imaging have been utilized for diagnosing and staging Pancoast tumors, there have been almost no reports on the efficiency of whole-body bone scans (WBBS) for detecting the level of abnormality in cases of superior sulcus tumors. CASE REPORT: We describe a case of Pancoast tumor in which technetium-99m methylene diphosphonate (Tc-99m MDP) bone single-photon emission-computed tomography (SPECT) was able to accurately detect multiple areas of abnormality in the vertebrae and ribs. In describing this case, we stress the clinical and diagnostic points, in the hope of stimulating a higher degree of suspicion and thereby facilitating appropriate diagnosis and treatment. From the results of this study, further clinical trials to evaluate the potential of SPECT as an efficient imaging tool for the work-up on cases of Pancoast tumor are recommended.